Encapsulation of CsPb2Br5 in TiO2 Microcrystals to Enhance Environmental Stability - Yuezhu Wang; Xiaotong Xu; Wenchao Yang; Yawen Wei; Junsheng Wang (Micromachines, 2023)
All-inorganic lead halide perovskite has emerged as an attractive semiconducting material due to its unique optoelectronic properties. However, its poor environmental stability restricts its broad application. Here, a simple method for the fabrication of CsPb2Br5/TiO2 is investigated. The introduction of p-aminobenzoic acid, which has two functional groups, is critical for the capping of amorphous TiO2 on CsPb2Br5. After calcination at 300 °C, amorphous TiO2 crystallizes into the anatase phase. The CsPb2Br5/TiO2 NCs show high long-term stability in water and enhanced stability against ultraviolet radiation and heat treatment, owing to the chemical stability of TiO2. More importantly, photo-electrochemical characterizations indicate that the formation of TiO2 shells can increase the charge separation efficiency. Hence, CsPb2Br5/TiO2 exhibits improved photoelectric activity owing to the electrical conductivity of the TiO2 in water. This study provides a new route for the fabrication of optoelectronic devices and photocatalysts based on perovskite NCs in the aqueous phase. Furthermore, the present results demonstrate that CsPb2Br5/TiO2 NCs has considerable potential to be used as a photoelectric material in optical sensing and monitoring.